2020
DOI: 10.3390/en13030697
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Forms and Supply Mode on Lipid Production of Microalga Scenedesmus obliquus

Abstract: Optimization of the microalgae culture conditions could significantly reduce the production costs of microalgae-derived biodiesel. In the current study, a new process of adding different forms using the multiple small-dose method was employed. The effects of different forms of nitrogen (NaNO3, NH4Cl, and CH4N2O) and their concentrations (0.1, 0.5, 1, and 2 mg L−1) on the growth and lipid production of Scenedesmus obliquus were studied. Algae density and lipid production increased with increasing nitrogen conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…Effect of different nitrogen concentrations (0, 36, 72, 144 and 288 mg/L) on the growth rate and biochemical composition Growth decreased in nitrogen-deficient conditions; in contrast, carbohydrates and fatty acids showed the highest value, 47% and 75%, respectively [7] Scenedesmus obliquus Various nitrogen concentrations' effect on growth and lipid production Lipid production increased with increasing nitrogen concentration; the highest cell density (1.7 × 10 7 cells/mL) and lipid production (242.4 mg/L) [33] Zhu et al [3] reported that Chlorella zofingiensis showed rapid growth in nitrogensufficient culture medium, whereas growth inhibition under nitrogen starvation conditions was observed. Upon nitrogen starvation, lipid accumulation increased greatly in C. zonfingiensis cells, which is desirable for biodiesel generation.…”
Section: Galbanamentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of different nitrogen concentrations (0, 36, 72, 144 and 288 mg/L) on the growth rate and biochemical composition Growth decreased in nitrogen-deficient conditions; in contrast, carbohydrates and fatty acids showed the highest value, 47% and 75%, respectively [7] Scenedesmus obliquus Various nitrogen concentrations' effect on growth and lipid production Lipid production increased with increasing nitrogen concentration; the highest cell density (1.7 × 10 7 cells/mL) and lipid production (242.4 mg/L) [33] Zhu et al [3] reported that Chlorella zofingiensis showed rapid growth in nitrogensufficient culture medium, whereas growth inhibition under nitrogen starvation conditions was observed. Upon nitrogen starvation, lipid accumulation increased greatly in C. zonfingiensis cells, which is desirable for biodiesel generation.…”
Section: Galbanamentioning
confidence: 99%
“…Nitrogen-deficient culture conditions produced two-fold lipids compared to nitrogen-sufficient medium as reported by Jia et al [ 30 ] and Pancha et al [ 29 ]. However, nitrogen depletion conditions can lead to the reduction of microalgae biomass productivity [ 33 ]. I. galbana was cultivated in different nitrogen concentrations to induced stress for lipid production.…”
Section: Microalgae Nutrient Compositionmentioning
confidence: 99%
“…The algae solution was centrifuged at 11,180×g for 6 min, and the algal residue was dried to constant weight at 60°C to collect dry algal matter. The lipid was extracted using the methanol-chloroform method described by An et al (2020). A precisely measured 100 mg of dried algae (W a ) was transferred into a 50 mL centrifuge tube, and 12 mL of a 1:2 chloroform-methanol solution was added.…”
Section: Analysis Of Cell Densitymentioning
confidence: 99%
“…Furthermore, it is possible that nitrogen limitation affects the lipid profile and several biochemical pathways of the cells [85][86][87].Therefore, new approaches, such as metabolic engineering, may be needed to increase the understanding of the effect of nitrogen on microalgae physiology and on the synthesis and accumulation of TGAs.…”
Section: Important Oleaginous Speciesmentioning
confidence: 99%